Organ Transplantation in Suspicious Death Case Forensic Medical and Ethical Issues - Demirer, Mustafa; Gürpınar, Süleyman Serhat; Küpeli, Ahmet; Çaylı, Erdinç; Baydar, Çetin Lütfi (The Bulletin of Legal Medicine, 2011)
Even if the developments in medical technology provide a second chance to the patients without any hope to live with organ transplantation, it has also resulted with the initiation of endless legal and ethical discussions. In this study, we aimed to discuss the legal and ethical issues rising from the transplantation of the organs collected from the donors whose brain death occured due to a suspicious condition. In this study, we have reviewed a case in which the organ transplantation process has been initiated following brain death occured after a suspicious condition reported as legal case to the Regulatory Authorities and to our department for the request of expert opinion. The current legal regulations, applications and the controversies inbetween were discussed. The brain death of a 2.5 year old female patient who had been found unconscious and transferred to the University Hospital's Intensive Care Unit was occured despite of all interventions after 8 days. During this period the reason of death could not be revealed and the case was reported to the legal authorities. Simultaneously the organ transplantation process was initiated and the Public Prosecutor was acknowledged. The forensic medicine specialists have been forced to decide between the legal responsibilities and the highest health interest and benefits. After the review of the medical documents, it was decided that the removal of the organs which were planned to be used in transplantation would not be effecting the results of the autopsy. The operation was done by the transplantation team and the liver and both kidneys were removed. The heart was left due to a possible cardiac disease. The autopsy was performed under these circumstances and the necessary samples were collected. The obligation of the autopsy for the determination of the reason of death, the necessity of the investigation of the organs removed for transplantation in order to understand the possible cause of death, the limitation of the time, the obtaining of the informed consent from the family were the medical and legal issues have to be adressed. Although the legal regulations associated with the organ transplantation maintain the compliance of the process to criminal law and solve the problems of reponsibility, this miraculous opportunity resulting from the organ transplantation offered by the developments in medicine and technology, was restricted by the conflict between regulations and principles of highest health interest and benefits. As a result all the parties involved were left in a difficult moral and legal situation.Key words: Forensic medicine, organ transplantation, autopsy.
Keywords: forensic medicine; organ transplantation; autopsy